Application of osmotic challenge for enrichment of microbial consortia in polyhydroxyalkanoates producing thermophilic and thermotolerant bacteria and their subsequent isolation - Pernicova, Iva; Novackova, Ivana; Sedlacek, Petr; Kourilova, Xenie; Koller, Martin; Obruca, Stanislav (International journal of biological macromolecules, 2020)
Polyhydroxyalkanoates are microbial polyesters which are considered being biological alternatives to petrochemical polymers. Extremophiles, such as thermophilic PHA producers, hold promise to improve competitiveness of PHA production process. Therefore, this work aimed at isolation of new strains, which could produce PHA under elevated temperature. Since traditional Nile red staining of colonies provided false positive results in thermophiles, we developed a novel strategy of enriching microbial consortia by PHA producers. This so called "osmoselective strategy" is based on application of osmotic challenge by sudden exposition of the mixed microbial culture to hypertonic and subsequently to hypotonic conditions; moreover, this strategy relies on the fact that PHA protect bacteria from negative effects of rapid fluctuations in osmotic pressure. In combination with fast and reliable ATR-FTIR inspection of selected colonies for presence of PHA, we were able to isolate several promising thermophilic or thermotolerant PHA producing strains belonging to the genera Bacillus, Aneurinibacillus and Chelatococcus, which indeed deserves further investigation to evaluate their potential for industrial production of PHA.
Keywords: DNA bakterií; fermentace; termotolerance; sekvence nukleotidů; Isolation of bacteria; osmóza; Bacillales; vysoká teplota; Hot Temperature; Microbial Consortia; Alphaproteobacteria; polyhydroxyalkanoáty; Enrichment; Thermotolerance; Thermophiles; Fermentation; DNA, Bacterial; Base Sequence; Bioreactors; Bacillus; Osmosis; Bacteria; Osmotic challenge; mikrobiální společenstva; bioreaktory; Polyhydroxyalkanoates